Effect of Variety and Planting Date on Cowpea Growth in Maize-Cowpea Intercrop in Southern Guinea Savannah, Kwara State (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
On-Farm Adaptive Methodology was used in conducting the present study in loffa and Offa. both situated  within the wet Savannah of Nigeria. The main objective of the study was to launch cowpea to the status of a major crop and farming system in the ecological. The cowpea varieties (ITZ-82-90-SAMPEA17, Ex-Borno and Ife Brown) were tested against three sowing dates. The data collected were subjected to ANOVA, and means were separated using LSD at the P≥0.05 level of significance. Variety × Sowing Date significantly (P ≤ 0.05) reduces days to 50% flower initiation to as low flowering was recorded from the interaction of Ife Brown with the individual sowing dates and the interaction of Ex-Borno versus the 3 sowing dates. The interaction of (the three) sowing dates and both Ife Brown and Ex-Borno resulted in a higher nodule count in the range of 52-61. Other morphological traits like plant height and relative growth rate were likewise significantly (P ≤ 0.05) influenced by variety × sowing date. The individual interaction of Ex-Borno and Ife Brown with sowing on 13/09/2023recorded the highest cowpea grain yield from the two locations of the experiment. An average cowpea grain yield of 1109 and 1106.5 kg/ha was recorded from Iloffa and Offa, respectively. Based on the findings, both Ife Brown and Ex-Borno were recommended for late sowing on the 13th of September in the wet Savannah.